Population Genetic Structure of Anisakis simplex Infecting the European Hake from North East Atlantic Fishing Grounds - Andrea Ramilo; Helena Rodríguez; Santiago Pascual; Ángel F. González; Elvira Abollo (Animals, 2023)
The European hake, one of the most commercially valuable species in ICES fishing areas, is considered an important neglected source of zoonotic risk by nematode parasites belonging to the genus Anisakis. Merluccius merluccius is, by far, the most important host of Anisakis spp. at the European fishing grounds, in terms of demographic infection values, and carries the highest parasite burden. These high parasite population densities within an individual fish host offer a chance to explore new sources of variations for the genetic structure of Anisakis spp. populations. A total of 873 Anisakis spp. third-stage larvae, originally sampled from viscera and muscular sections of hake collected at ten fishing grounds, were primarily identified using ITS rDNA region as molecular marker. After that, we used mtDNA cox2 gene to reveal the high haplotype diversity and the lack of genetic structure for A. simplex. Dominant haplotypes were shared among the different fishing areas and fish sections analyzed. Results indicate a clear connection of A. simplex from European hake along the Northern North Sea to the Portuguese coast, constituting a single genetic population but revealing a certain level of genetic sub-structuring on the Northwest coast of Scotland. This study also provides useful information to advance the understanding of parasite speciation to different fish host tissues or microenvironments.